Working classification of traumatic spinal stenosis for injuries of the lower thoracic and lumbar spine - A. A. Afaunov; A. V. Kuzmenko (Кубанский научный медицинский вестник, 2016)
To develop a working classification of traumatic spinal stenosis for injuries of the lower thoracic and lumbar spine. 170 patients with injuries of the lower thoracic and lumbar spine accompanied by traumatic spinal stenosis for 20052013. Decompressive-stabilizing operations with PSF were done for all patients. Priority was given to reposition indirect decompression. The dependence of the efficiency of the reformation of the spinal canal stenosis by morphological reasons was studied. This classification allows to predict for PSF the effectiveness of the reposition of the dural sac decompression by stretching ligaments. Reposition and decompression are most effective when compression of the dural sac by a single bone fragment back of the vertebral body or two large fragments without reversion to 10 days after injury, or if subluxation and dislocation in the early and intermediate periods of spinal cord injury.